LAPORAN KEGIATAN SEKOLAH DALAM MELAKSANAKAN PROGRAM PENGABDIAN KEPADA MASYARAKAT (PKM)TEMA SOSIALISASI:SOSIALISASI UNTUK MEMBENTUK KARAKTER SISWA-SISWI DALAM BERTOLERANSI DAN SOPAN SANTUN TERHADAP GURU - Yahya Nusa; Fransisca Takin; Rahmatan Lil Alamin; Salsabillah Nurdin (JOURNAL OF COMMUNITY DEDICATION, 2025)
This Community Service (PKM) activity was conducted to educate school students about the importance of character development, particularly the values ​​of tolerance and courtesy toward teachers. The background to this activity was the increasing diversity of moral and ethical issues in the school environment, which impact the relationship between students and teachers. The activity was implemented through a socialization approach, interactive discussions, and positive behavior simulations, which were participated in by all secondary school students. The results of the activity showed an increase in students' understanding of the importance of mutual respect, polite communication, and an increased awareness of maintaining harmonious relationships with teachers. In conclusion, this socialization successfully contributed positively to shaping students' character based on the values ​​of tolerance and courtesy. It is hoped that this will be the first step in creating a school culture that is ethical and moral.